The Role Of People-Centered Community Planning Towards Urban Kampung Sustainability: A Case Study On Industrial Clusters In Kampung Kauman And Sondakan Surakarta - N.H, Kusumaningdyah; Ramdhon, Akhmad (Fakultas Teknik, Universitas Brawijaya, 2015)
Surakarta is one of cities in Indonesia which implements an appropriate planning process and has a good condition for governance initiatives. Its planning process involves citizens participation in order to achieve sustainable development. This research aims to clarify the role of people centered community planning in Kampung Kauman and Kampung Sodakan as study cases. Method used Egan Wheel Diagram to measure the neighbourhood asset management. Result shows that the eight elements of Egan Wheel’s i.e.; social culture, governance, environtment, transportation, sercice, equality, economy, and neighborhood are appeared and elaborate. Both of key-persons are succeed to trigger people in two kampung get well initiative and involve in maintaning their community assets. Eventhough, youth community also have good willingness to manage and maintain their assets. From this research can be showed that building social capability is not a simple process, including defining skills and supplying training. Their successfull depends on the coordination and commitment of keyperson factors and local institutions.Keywords : kampung kota, citizen participation, Egan Wheel.